1H, 15N and 13C resonance assignments of the N-terminal domain of the nucleocapsid protein from the endemic human coronavirus HKU1 - de Luna Marques, Aline; Caruso, Icaro Putinhon [UNESP]; Santana-Silva, Marcos Caique; Bezerra, Peter Reis; Araujo, Gabriela Rocha; Almeida, Fabio Ceneviva Lacerda; Amorim, Gisele Cardoso (Springer Nature, 2021)
Coronaviruses have become of great medical and scientific interest because of the Covid-19 pandemic. The hCoV-HKU1 is an endemic betacoronavirus that causes mild respiratory symptoms, although the infection can progress to severe lung disease and death. During viral replication, a discontinuous transcription of the genome takes place, producing the subgenomic messenger RNAs. The nucleocapsid protein (N) plays a pivotal role in the regulation of this process, acting as an RNA chaperone and participating in the nucleocapsid assembly. The isolated N-terminal domain of protein N (N-NTD) specifically binds to the transcriptional regulatory sequences and control the melting of the double-stranded RNA. Here, we report the resonance assignments of the N-NTD of HKU1-CoV.
Keywords: HKU1; Human betacoronavirus; N-terminal domain; NMR assignment; Nucleocapsid protein